2019
DOI: 10.3390/su11195281
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prediction Accuracy under the Selection of Optimum Time Granularity in Different Metro Stations

Abstract: The improvement of accuracy of short-term passenger flow prediction plays a key role in the efficient and sustainable development of metro operation. The primary objective of this study is to explore the factors that influence prediction accuracy from time granularity and station class. An important aim of the study was also in presenting the proposition of change in a forecasting method. Passenger flow data from 87 Metro stations in Xi’an was collected and analyzed. A framework of short-term passenger flow ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The experimental data are the inbound and outbound passenger flow data of Yangji Station of Guangzhou Metro from 1 July 2019 to 28 July 2019 from 6:15 to 23:15. The time series was smoothed by aggregating flow data into nonoverlapping 15-min intervals [ 38 ]. This resulted in 96 samples per day.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental data are the inbound and outbound passenger flow data of Yangji Station of Guangzhou Metro from 1 July 2019 to 28 July 2019 from 6:15 to 23:15. The time series was smoothed by aggregating flow data into nonoverlapping 15-min intervals [ 38 ]. This resulted in 96 samples per day.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [17] proposed to generate multi-day activity-travel data through sampling from readily available single-day household travel survey data. Li et al [18] indicated that the time granularity of the prior passenger flow data and the difference in site classification will also lead to differences in prediction accuracy. Ma et al [19] explored the distribution of passenger spatiotemporal characteristics based on big data of traffic smart cards, laying a foundation for the selection of passenger flow prediction objects.…”
Section: A the Data Selection Workmentioning
confidence: 99%
“…They study the time granularity from one minute to 24 hours, and the result indicates that when time granularity changes within one minute to 15 minutes, the regularity coefficient increases significantly, and when the time granularity is more than 15 minutes, the change of regularity coefficient is flat. Li et al (2019) analyse the similarity coefficients of passenger flow under different time granularity for Xi'an subway stations. They conclude that the similarity coefficient of passenger flow increases significantly within the time granularity of 5 minutes to 15 minutes, and when the time granularity is more than 15 minutes, the similarity coefficient of the passenger flow changes insignificantly.…”
Section: Introductionmentioning
confidence: 99%